1999
DOI: 10.1359/jbmr.1999.14.4.583
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium and Bone Density in Adolescent Girls and Young Women in Europe

Abstract: The objective of this study was to investigate the association between dietary calcium intake and radial bone density among young women, over the whole range of intake and at different levels of calcium intake. The study design was a cross-sectional, observational multicenter investigation in six European countries. One thousand one hundred and sixteen healthy Caucasian girls aged 11-15 years and 526 women aged 20-23 years participated, after having been selected from larger population samples to represent a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 31 publications
2
32
3
Order By: Relevance
“…Another interventional trial by Johnston et al [30] suggested that additional dietary Ca would only a ect BMD in prepubertal children. Similar ®ndings have recently been reported by Kardinaal et al [8]. Failure to ®nd consistent associations between calcium and bone may also be attributed to high mean Ca intakes within this cohort.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another interventional trial by Johnston et al [30] suggested that additional dietary Ca would only a ect BMD in prepubertal children. Similar ®ndings have recently been reported by Kardinaal et al [8]. Failure to ®nd consistent associations between calcium and bone may also be attributed to high mean Ca intakes within this cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, despite extensive research, the calcium-bone relationship remains controversial. Calcium intake has been cited by many authors as a major contributor to increased bone mineral measures [6,28], whereas others have reported no association [7,8]. In the current study, Ca intakes reported by the females at adolescence showed a significant positive association with BMD (femoral neck) measured at young adulthood.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Among European girls, the mean calcium intake varied between 600 mg/d in Italy and 1,250 mg/d in Finland (Kardinaal et al, 1999). The intake of calcium in adult women was in a similar range.…”
Section: Calcium and Vitamin Dmentioning
confidence: 92%
“…Despite an adequate Ca intake of young adults estimated by the Institute of Medicine to be 1,000 mg/day, the 1994 Continuing Survey of Food Intake of Individuals (CSFII) data and the Third National Health and Nutrition Examination Survey (NHANES III) showed the Ca intakes of women in their 20s in the United States to be only 647 (Standing Committee on the Scientific Evaluation of Dietary Reference Intakes 1997) and 768 mg/day (Bialostosky et al 2002), respectively. Average Ca intakes of young women aged 20-23 years in six European countries ranged from 680 to 1,236 mg/day (Kardinaal et al 1999). In comparison with these data, the Ca intakes of our subjects were much less; approximately half of that of young female populations with low Ca intake in Western countries.…”
Section: Discussionmentioning
confidence: 46%